Health and temperaments of cloned working dogs - Kim, Min Jung; Oh, Hyun Ju; Hwang, Sun Young; Hur, Tai Young; Lee, Byeong Chun (Journal of veterinary science (Suwŏn-si, Korea), 2018)
Dogs serve human society in various ways by working at tasks that are based on their superior olfactory sensitivity. However, it has been reported that only about half of all trained dogs may qualify as working dogs through conventional breeding management because proper temperament and health are needed in addition to their innate scent detection ability. To overcome this low efficiency of breeding qualified working dogs, and to reduce the enormous costs of maintaining unqualified dogs, somatic cell nuclear transfer has been applied in the propagation of working dogs. Herein, we review the history of cloning working dogs and evaluate the health development, temperaments, and behavioral similarities among the cloned dogs. We also discuss concerns about dog cloning including those related to birth defects, lifespan, and cloning efficiency.